PERANCANGAN APLIKASI ABSENSI KELAS PRESENTENSE.COMSCI BERBASIS GLIDE SEBAGAI PLATFORM NO-CODE - Evelyn Keisha Silalahi; Aurela Khoiri Nasution; Josua Anugrah Deo Tampubolon; Rut Kezia Imburi; Adidtya Perdana (LPPM Universitas Dhyana Pura, 2026)
The development of information technology has encouraged the birth of digital solutions in various fields, including education. One of the problems often faced in the academic environment is a manual attendance system that is prone to manipulation, inefficient, and makes it difficult to record data. This research aims to design and implement a mobile-based digital attendance application called Presentense.ComSci, using Glide as a no-code platform. The research method used is Research and Development (R&D), with stages ranging from needs analysis, system design, implementation, to evaluation. This application is designed to be able to record student attendance in real-time through the institution's email verification feature, automatic time recording (timestamp), GPS location tracking, and selfie upload as proof of attendance. Attendance data is automatically saved into a Google Spreadsheet, so it can be accessed by the admin practically and safely. Tests were conducted on two classes at Medan State University with the results showing that the application was able to function properly, although there were some problems with GPS location accuracy. With this application, the attendance recording process becomes more transparent, efficient, and practical, and can be an innovative solution for attendance management in higher education.